2019
DOI: 10.1002/cbic.201900664
|View full text |Cite
|
Sign up to set email alerts
|

The Two Classic Pb2+‐Selective DNAzymes Are Related: Rational Evolution for Understanding Metal Selectivity

Abstract: In 1994, the first DNAzyme namedG R5 was reported,w hich specifically requires Pb 2 + for its RNA cleavage activity.T hree years later,the 8-17 DNAzyme was isolated. The 8-17 DNAzyme and the related 17E DNAzyme are also most active with Pb 2 + , although other divalent metals can work as well. GR5 and 17E have the same substrates equence, and their catalytic loopsi n the enzyme strandsa lso have af ew similar and conserved nucleotides. Considering these, we hypothesizedt hat 17E might be aspecial form of GR5. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Some of the most extensively studied DNAzymes contain the 8–17 motif. Extensive biochemical assays have been carried out using various metal cofactors, ,, DNAzyme core mutation, and a change in the substrate cleavage junction . The same motif has been reported for many different selection conditions by multiple research groups.…”
mentioning
confidence: 98%
“…Some of the most extensively studied DNAzymes contain the 8–17 motif. Extensive biochemical assays have been carried out using various metal cofactors, ,, DNAzyme core mutation, and a change in the substrate cleavage junction . The same motif has been reported for many different selection conditions by multiple research groups.…”
mentioning
confidence: 98%
“…Based on these components, we analyzed the next-generation sequencing (NGS) sequences from the in vitro selected DNAzyme library. Since the secondary structure of the 11-5 DNAzyme is similar to that of the 8-17 DNAzyme, we have also compared known variants of the 8-17 DNAzyme. , From these analyses, we identified potential nucleotides in the catalytic domain of the 11-5 DNAzyme and performed site-specific mutations targeting these nucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…[40] Recent studies showed that 17E might be a special form of GR5. [41,42] More recently, a Na + -specific DNAzyme named NaA43 was reported (Figure 1D), which works without the need of any divalent metal ion. [43] Its specificity for Na + was from an aptamer motif, [44][45][46][47] and a few other DNAzymes also contain this aptamer motif.…”
Section: Dnazymesmentioning
confidence: 99%